-2(y-6)=-7y+7

Simple and best practice solution for -2(y-6)=-7y+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(y-6)=-7y+7 equation:



-2(y-6)=-7y+7
We move all terms to the left:
-2(y-6)-(-7y+7)=0
We multiply parentheses
-2y-(-7y+7)+12=0
We get rid of parentheses
-2y+7y-7+12=0
We add all the numbers together, and all the variables
5y+5=0
We move all terms containing y to the left, all other terms to the right
5y=-5
y=-5/5
y=-1

You can always share this solution

See similar equations:

| -8w+40=-2(w-2) | | -9(w-8)=4w+7 | | 3x-13=7(x=2)-4(x-7) | | 3x-13=7(x=2)-4 | | (5x+5)/10=-4 | | X+x-1=5x | | -(2x-6)+10x=-5x-3(-7x-7) | | 6w-3w/2=-12 | | 60+x+x+2x+15=180 | | -5+2n=11 | | 7-y/2=6 | | 60+x+x+2x+15=360 | | 7x+9=8x-1 | | 5-g/2=12 | | (A+28)+2a=180 | | 0.2(5x+1)=26 | | 2(5x+3)=31 | | 125x=32.2 | | 5t^2+9t-11=0 | | 3(2x-0.4x)=18 | | 18(x)+350(16-)=114 | | 18x-(7/2)x=158 | | 1/5(25+15x)=44 | | 90x-180=810 | | 10(8x-6)=10 | | 50+75=3x+4 | | 8(4x-2)=5 | | 5x+11=7x | | 24k=24k-11 | | 3/5u+9=5 | | -8=x+10=-3x | | -8=x+2=-3x |

Equations solver categories